A MULTICENTER ICET-A STUDY ON AGE AT MENARCHE AND MENSTRUAL CYCLES IN PATIENTS WITH TRANSFUSION-DEPENDENT THALASSEMIA (TDT) WHO STARTED EARLY CHELATION THERAPY WITH DIFFERENT CHELATING AGENTS. - SALVATORE DI MAIO; VINCENZO DE SANCTIS; PIERLUIGI MARZUILLO; CHRISTOS KATTAMIS; SHAHINA DAAR; MEHERAN KARIMI; SAKI FOROUGH; ATANAS BANKEV; VALERIA KALEVA; SOTEROULA CHRISTOU; CARMELO FORTUGNO; POLYXENI DELAPORTA; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract. Objective: To evaluate the age at menarche and menstrual characteristics in patients with transfusion-dependent thalassemia (TDT) who started early chelation therapy (≤ 3 years) with a variety of chelating agents. Design: A retrospective multicenter study promoted by International Network of Clinicians for Endocrinopathies in Thalassemia and Adolescent Medicine (ICET-A). Setting: Eight of 13 International Thalassemia Centers (61.5%) in the ICET-A Network participated. Patients: Fifty-seven female TDT patients, aged 11 to 26 years, were enrolled in the study. Seven patients were excluded, 4 who were still prepubertal (age 12-14 years) and 3 with primary amenorrhea.  The remaining 50 patients were from Iran (33 patients), 9 from Bulgaria, 8 from Greece, 4 from Oman, 2 from Cyprus, and 1 from Italy. Results: At start of chelation therapy, 22 patients received desferrioxamine mesylate (DFO), 26 deferasirox (DFX) and 2 deferiprone (DFP). All fifty TDT patients developed spontaneous menarche at a mean age of 14.2 ± 2.24 years (range 9 – 20). A significant positive correlation was observed between age at menarche and serum ferritin (SF) levels (r: 0. 41, P: 0.005). Thirty-two patients (64%) reported regular menstrual cycles, 7 (14 %) oligomenorrhea, 3 (6%) short/light menses (hypomenorrhea), and 8 (16%) secondary amenorrhea (SA) (16%). Conclusions: Early chelation does not necessary correlate with efficient chelation during pubertal age. Delayed menarche, related to high SF levels, was still frequent in most Centers and was a forerunner of irregular menstrual cycles, SA and associated complications. Neglecting the importance of adherence to iron chelation therapy (ICT), despite innovative and expensive therapies, may lead to complications and decreased quality of life.